Diseño y simulación de una cámara de secado para tuberías pintadas en acero negro A-53 y cobre ASTM B88, utilizando energía solar y un sistema auxiliar de GLP - Campaña Ramírez, Edison Xavier (2016)
All metallic pipes which company uses must have a coating for achieve color codes requirement. The company is used to doing this process with workmanship and dry process is for natural environment. With purpose of improve the drying time company needs to change this process, so we propose the design and simulation of a drying device for painted pipes. The operating system is based on the Heat Transfer theory. The pipes are arranged over a support with cross flow air-water. The chamber has been designed with a volume of 60 m³. The inside air is distributed through the shelves of painted pipes where it is driven for two axial fans of 120 CFM. A catchment area of 8m² was defined for plane plate solar collectors (4 units). The auxiliary heating system is designed with a tankless heater of 6 liters. The water temperature in the system shall be 60-90 Celsius degrees. This simulation was made with a cfd software (CFD Simulation-Autodesk) wich confirms all design factors. System's total energy (solar and gas) satisfies the required demand in the indoor of the chamber and it is 3kW/h.